LIBERTARIANISM OR PROPERIALISTISM? SELF-OWNERSHIP AS THE FOUNDATION OF ROBERT NOZICK'S LIBERTARIAN THEORY (2024) - Gomes, Victor Henrique Ahlf (Seven Editora, 2026)
The present work aims to understand the theoretical foundations of the famous political philosophy developed by Robert Nozick in his work Anarchy, State and Utopia, addressing and defining the nature of the concept of self-ownership and the role it plays in libertarian argumentation, as well as the way in which the author is able to extract his “strong theory of rights” from it. During this study, we propose the thesis that self-ownership is seen in Nozick as a quaestio facti, and not just as a principle subordinate to the Kantian categorical imperative, as his critics claim. Important conclusions will emerge from this thesis, which, in our view, make the author's libertarian theory much more attractive and appealing than if we take his fundamental position as a mere principle. Among these lessons is that, although Anarchy, State and Utopia is routinely defined as libertarian, an epithet that suggests freedom with an unparalleled status in his work, its true foundation is found in self-ownership as a fact, in the private property rights arising from it and in the negative rights (side constraints) that arise from both.DOI: https://doi.org/10.56238/sevened2026.008-117